Does Fracture Pattern Influence Thoracic Trauma? - Houlton, J. E. F.; Dyce, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
The case records of 300 dogs presented for fracture repair following road traffic accident (RTA) or other trauma were studied to determine possible relationships between specific patterns of skeletal trauma and the prevalence of thoracic wall and pulmonary injury.A significantly greater proportion of dogs involved in RTA (31%) sustained thoracic trauma compared ro those injured by other means (2.4%). Although RTA cases were more likely to suffer multiple fractures (23%), there was no significant relationship between the incidence and distribution of a fracture(s) and radiographic evidence of thoracic trauma.Of those dogs with thoracic trauma, pneumothorax and pulmonary contusion were the most frequent injuries; more than one type of injury occurred in 43% of these cases.Clinical management was altered as a result of thoracic injury in 24% of these cases.In a retrospective survey of 300 dogs presented for fracture repair, there was no significant relationship between fracture pattern and the prevalence of thoracic trauma. Following road traffic accident, radio-graphic examination revealed thoracic trauma in 31% of dogs. Clinical management was modified as a result of thoracic injury in 24% of cases.
Keywords: Thoracic trauma; fracture pattern